HUBUNGAN MOTIVASI DAN PENGETAHUAN TENTANG PMTCT (PREVENTION OF MOTHER-TO CHILD TRANSMISSION OF HIV) DENGAN KESEDIAAN MENGIKUTI PMTCT PADA IBU HAMIL PENDERITA IMS (INFEKSI MENULAR SEKSUAL) DI KABUPATEN PATI - Yuli Irna Wati; Retno Wulan (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Prevention Mother to Child Transmission (PMTCT) is a government program to prevent transmission of the HIV / AIDS virus from mother to baby. The use of PMTCT will run well if the government and health workers can find out what are the obstacles in the motivation of pregnant women to participate in PMTCT. If PMTCT can run well, the transmission of HIV / AIDS can be suppressed / reduced. Ironically, if pregnant women with STIs feel that they do not need to participate in PMTCT, it is likely that the use of PMTCT will not work well, as a result the transmission of HIV / AIDS cannot be prevented and will increase. The purpose of this study was to determine the relationship between motivation and knowledge about PMTCT and willingness to take part in PMTCT. The population in this study were all pregnant women who experienced STIs in Pati, while the sampling technique in this study used total sampling, while the sample in this study were 32 pregnant women in Pati Regency. This type of research is a survey with a cross-sectional approach whose measuring instrument is a questionnaire containing knowledge, motivation and willingness to take part in PMTCT which will be tested for validity and reliability and distributed to respondents. Data were analyzed using the Chi Square test to determine the relationship between the two variables. The independent variable is the knowledge and motivation of pregnant women, while the dependent variable is the willingness to follow PMTCT. The results showed that there was a relationship between the knowledge and motivation of pregnant women with the behavior of doing PMTCT services, this can be seen from the asymp.sig (2 side) value of the Pearson chi square test which was 0.000 <0.05, so that Ha was accepted and Ho was rejected.